PERANAN PIHAK LEMBAGA PEMASYARAKATAN TERHADAP RESIDIVIS YANG MELAKUKAN TINDAK PIDANA PENCURIAN - Andhika Abrian (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT The factors that cause crime generally consists of 2 (two), namely: Internal factors, namely the factors contained within the human self itself include: religious factors, education; External factors, namely factors that come from outside the human person which includes: family environment, community environment, economic factors. As for the efforts of crime prevention consists of two aspects, the first in terms of prior crimes that are often known by the preventive way, and second in terms of after the occurrence of crime that is in a repressive way. Factors that cause the occurrence of recidivism is an interrelated factor. Either because of educational, community or economic factors. Meanwhile, according to the recognition of the recidivist itself, that the outcome of the crime is for dissipation, especially for himself and his friends who are negative. All these actions are inseparable from the influence of the surrounding environment and the lack of religious knowledge, and the low level of education. Plus no income after he left the Penitentiary. In addition, there is also the influence of association that gives opportunity for the repetition of the crime. As for the prevention efforts undertaken by the Penitentiary Samarinda to prevent the occurrence of repetition of crime or recidivists is to conduct coaching in all areas that he thinks should be given to inmates. Coaching according to the author is already maximal. If there will be a former prisoner who commits his act again, it will only depend on each individual person who in this case is the former prisoner. Also regarding the fostering of ordinary prisoners with convict prisoners there is no particular distinction.